2003
DOI: 10.1021/ja035232n
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed Hydration and Hydroalkoxylation of Activated Olefins:  Use of a Strong Nucleophile to Generate a Strong Base

Abstract: The direct addition of water and a variety of alcohols to activated olefins was observed in the presence of nucleophilic phosphine catalysts. Unlike existing methods, the reactions proceed at room temperature and in the absence of transition metals, or strong acids or bases. The use of simple commercially available catalysts makes this an attractive method for the preparation of beta-hydroxy and beta-alkoxy substrates, which are prevalent targets and intermediates in organic synthesis. The scope and mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(174 citation statements)
references
References 17 publications
9
159
2
4
Order By: Relevance
“…The latter adds to the activated alkenes [361]. The reaction has been extended to other carbon acids than 2-nitropropane [362,363]. In 1992, Trost and Kazmaier [364] reported that Ph 3 P catalyzes the isomerization of conjugated ynones, ynoates and ynecarboxamides (113) into conjugated dienes 121 (Scheme 56).…”
Section: Umpolung Of Michael Acceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter adds to the activated alkenes [361]. The reaction has been extended to other carbon acids than 2-nitropropane [362,363]. In 1992, Trost and Kazmaier [364] reported that Ph 3 P catalyzes the isomerization of conjugated ynones, ynoates and ynecarboxamides (113) into conjugated dienes 121 (Scheme 56).…”
Section: Umpolung Of Michael Acceptorsmentioning
confidence: 99%
“…The latter adds to the activated alkenes [361]. The reaction has been extended to other carbon acids than 2-nitropropane [362,363]. In 1992, Trost and Kazmaier [364] reported that Ph3P catalyzes the isomerization of conjugated ynones, ynoates and ynecarboxamides (113) The proposed mechanism implies the formation of carbanionic intermediates (e.g., 114 ⇄ 115; 117 ⇄ 118 ↔ 119 ⇄ 120) resulting from protonation and deprotonation of zwitterionic phosphonium intermediates [99].…”
Section: Umpolung Of Michael Acceptorsmentioning
confidence: 99%
“…5,6 Indeed, the reducing capabilities of phosphines as well as their ability to serve as initiators/catalysts for Michael conjugate addition reactions is well documented. [55][56][57] The products from the thiol-ene reaction, PNIPAm 50 -S-ALMA and PNIPAm 50 -S-PROPA, were characterized using a combination of 1 H NMR spectroscopy and SEC, Figure 2 and Table 1. b, the resonance associated with the methine group of the isopropyl side chains, indicates a DP of 52.…”
Section: (B)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] There are a few examples about the selectivity tuning for the reaction of hydroxybenzenes with α,β-unsaturated compounds, however, these precedents did not give satisfactory results. Rudolf Aumann discovered that both oxa-Michael adduct and Friedel-Crafts alkylated product were produced from the reaction of 9-phenanthrol, while the reaction of phenol only afforded the oxa-Michael adduct.…”
Section: Introductionmentioning
confidence: 99%